Diabetes in Panama: Epidemiology, Risk Factors, and Clinical Management - Anselmo J Mc Donald Posso; Ryan A Bradshaw Meza; Enrique A Mendoza Morales; Ycly Jaen; Alberto Cumbrera Ortega; Enrique Jorge Mendoza Posada (Ubiquity Press, 2016)
Objectives To draw evidence-based conclusions about the epidemiology, drivers, and management of diabetes in Panama based on a literature review and original analyses of large databases. Methods A search about diabetes in Panama was conducted through PubMed. We used the final reports of 2 studies: the first Survey of Health and Life Quality, 2007, and the first Survey of Risk Factors Associated to Cardiovasular Diseases, 2010-2011, conducted in Panama and analyzed the databases. We reviewed the approach adopted by the Panamanian Social Security institution and the diabetes national guidelines published by the Panamanian Ministry of Health. Findings The prevalence of diabetes, as estimated in 1 database (ENSCAVI), was 5.4% (4.3% men; 6.0% women; OR = 1.41 [confidence interval 1.26-1.59]; 'P' < 0.0001), with the highest prevalence in urbanized regions. In another database (PREFREC), prevalence was 9.5% (10.3% men and 9.1% women), again higher in urbanized regions, but also in males, older adults, and Afro-Panamanians. Obesity, abdominal obesity, physical inactivity, family history of diabetes, high blood pressure, and triglycerides ≥ 150 mg/dL were associated as risk factors for diabetes in both genders ('P' < 0.0001). Total cholesterol ≥ 200 mg/dL and high-density lipoprotein cholesterol < 40 mg/dL were risk factors in men ('P' < 0.0001). In the last 5 years, diabetes was ranked between the sixth and fifth cause of death in Panama. In response, the Panamanian Social Security created the "Program for Prevention and Control of Diabetes" to strengthen primary health care. Conclusions Diabetes is a serious national public health threat in Panama. To address this problem in a public health modality, information from large databases was analyzed and presented to the Panamanian Ministry of Health to prompt constructive policy change to enhance diabetes prevention.